On the correlation structure of microstructure noise in theory and practice - Francis X. Diebold; Georg H. Strasser (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We argue for incorporating the financial economics of market microstructure into the financial econometrics of asset return volatility estimation. In particular, we use market microstructure theory to derive the cross-correlation function between latent returns and market microstructure noise, which feature prominently in the recent volatility literature. The cross-correlation at zero displacement is typically negative, and cross-correlations at nonzero displacements are positive and decay geometrically. If market makers are sufficiently risk averse, however, the cross-correlation pattern is inverted. Our results are useful for assessing the validity of the frequently-assumed independence of latent price and microstructure noise, for explaining observed cross-correlation patterns, for predicting as-yet undiscovered patterns, and for making informed conjectures as to improved volatility estimation methods.
urn:nbn:de:hebis:30-58883
Keywords: G14; G20; D82; D83; C51; 330; Realized Volatility; Market Microstructure Theory; High-Frequency Data; Financial econometrics; Finanzmarkt; Ökonometrie; Mikrostrukturanalyse; Kapitalertrag; Volatilität; Theorie